2017
DOI: 10.1200/jco.2017.35.15_suppl.e15076
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of Oncotype DX in early stage colon cancer.

Abstract: e15076 Background: With the advent of colon cancer screening, patients with early stage colon cancer will be more common in our clinics. The evidence supporting the absolute benefit of chemotherapy in resected Stage II and (to a lesser extent) Stage IIIA disease is poor. Not all patients benefit from chemotherapy and toxicity is a problem. There is a need for validated biomarkers to assess individual patient recurrence risk and discriminate absolute treatment benefit. Several studies have validated the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The similar assays are being tested in prognosis of colon cancer. The twin test of Oncotype DX ® used in breast cancer – 12-gene Oncotype DX ® Colon Cancer Assay identifies the tumors with high risk of recurrence and helps to determine the necessity of implementation of adjuvant systemic therapy [ 182 , 183 , 184 ]. In the study of Aziz et.…”
Section: Applications Of Transcriptome Analysis In Oncologymentioning
confidence: 99%
“…The similar assays are being tested in prognosis of colon cancer. The twin test of Oncotype DX ® used in breast cancer – 12-gene Oncotype DX ® Colon Cancer Assay identifies the tumors with high risk of recurrence and helps to determine the necessity of implementation of adjuvant systemic therapy [ 182 , 183 , 184 ]. In the study of Aziz et.…”
Section: Applications Of Transcriptome Analysis In Oncologymentioning
confidence: 99%
“…The data from the National Surgical Adjuvant Breast and Bowel Project C-07 study suggest that genomic profiling using the Oncotype dx assay (Genomic Health, Redwood City, CA, U.S.A.) might improve risk prognostication in high-risk resected stage ii and iii colon cancers 39 . A recent study demonstrated that Oncotype dx results altered the decision about adjuvant chemotherapy use in 27% of patients with stages ii and iiia-b crcs and that its results might be applicable in decision-making for adjuvant therapy in elderly patients 40 .…”
Section: Genomic Profilingmentioning
confidence: 99%